The results of experimental studies of extrusion of feed containing wheat grain and black soldier fly larvae biomass - V. I. Pakhomov; S. V. Braginets; O. N. Bakhchevnikov; A. S. Alferov; A. I. Rukhlyada; A. S. Babajanyan (Аграрная наука Евро-Северо-Востока)
The experimental studies were carried out in the Rostov region of Russia in 2019. Three variants of grinded wheat grain mixed with biomass of black soldier fly larvae with raw animal material content of 10, 12.5 and 15 % by mass were extruded at varying temperature. The content of amino acids in raw material and finished extrudate was determined. It has been established that the feed mixture containing grinded wheat grain and biomass of black soldier fly larvae can be successfully extruded at the temperature of 121-135 ºC. As the extrusion temperature rises in the range of 115º-140 ºС, the content of amino acids in a finished extrudate decreases. Change in larvae content in the feed mixture does not affect the nature of the correlation between the amino acids content in the extrudate and the extrusion temperature and process behavior. It has been found that with increasing temperature the amino acids content in the extruded feed decreases with an accelerated velocity irrespective of the insect biomass content. The rational temperature range for extrusion of feed mixture containing grinded wheat grain and larvae biomass was determined within 121-127 ºC. This range provides no more than 30 % decrease in indispensable amino acids content in the extrudate. The extruded feed containing 15% of insect larvae biomass contains 9.6±0.13 % of amino acids, including 4.38±2.01 % of indispensable amino acids. Extrusion of larvae biomass mixed with grain of cereal crops is considered to be a promising direction for improving production of feed for fish and farm animals.